Influence of Cu(II) in the SrSnO3 crystallization - Melo, D.; Marinho, R. M. M.; Vieira, F. T. G.; Lima, S. J. G.; Longo, Elson [UNESP]; Souza, A. G.; Maia, A. S.; Santos, I. M. G. (Springer, 2011)
Perovskite type oxides have been intensively studied due to their interesting optical, electrical, and catalytic properties. Among perovskites the alkaline earth stannates stand out, being strontium stannates (SrSnO3) the most important material in ceramic technology among them due to their wide application as dielectric component. SrSnO3 has also been applied as stable capacitor and humidity sensor. In the present work, SrSnO3:Cu was synthesized by polymeric precursor method and heat treated at 700, 800, and 900 A degrees C for 4 h. After that, the material was characterized by thermal analysis (TG/DTA), X-ray diffraction (XRD), infrared spectroscopy, and UV-vis spectroscopy. Results indicated three thermal decomposition steps and confirmed the presence of strontium carbonate and Cu2+ reduction to Cu+ at higher dopant amounts. XRD patterns indicated that the perovskite crystallization started at 700 A degrees C with strontiatite (SrCO3) and cassiterite (SnO2) as intermediate phases, disappearing at higher temperatures. The amount of secondary phase was reduced with the increase in the Cu concentration.
Keywords: Strontium stannate; Copper; TG/DTA; Polymeric precursor method and perovskite